Attitude towards Antipsychotic Medications in Patients Diagnosed with Schizophrenia: A Cross-Sectional Study at Amanuel Mental Specialized Hospital, Addis Ababa, Ethiopia. (22nd May 2019) - Kassew, Tilahun; Demilew, Demeke; Birhanu, Addis; Wonde, Mesele; Liyew, Biks; Shumet, Shegaye
Abstract : Background . Poor attitude towards antipsychotic drugs is high, and it is a factor for non-adherence to treatment. This increases the risk of relapse, associated healthcare utilization, and costs. This study aimed to assess attitude towards antipsychotic medication among patients with schizophrenia. Objectives . The aim of this institution based cross-sectional study was to assess attitude towards antipsychotic medications and associated factors among patients with schizophrenia who attend the outpatient clinics at Amanuel Mental Specialized Hospital, 2018. Methods . In a cross-sectional study, 393 schizophrenic patients from Amanuel Mental Specialized Hospital were recruited by a systematic random sampling technique. Drug Attitude Inventory (DAI-10) was used to assess attitude, experience, and belief about antipsychotics. Glasgow antipsychotic side effect scale modified version, positive and negative syndrome scale, and Birch wood's insight scale for psychosis were the instruments used to assess the associated factors. Simple and multiple linear regression analysis models were fitted, and the adjusted unstandardized beta ( β ) coefficient at 95% confidence interval was used. Results . The mean score of attitude towards antipsychotic medications was 6.51 with standard deviation (SD) of 2.22. In multiple linear regression, positive symptoms ( β = -0.07, 95% CI: (-0.09, -0.05)), negative symptoms ( β = -0.04, 95% CI: (-0.06, -0.02)), shorter (≤5 years) duration of illness ( β = -0.39, 95% CI: (-0.63, -0.15)), first generation antipsychotics ( β = -0.35, 95% CI: (-0.55, -0.14)), having sedation ( β = -0.28, 95% CI: (-0.52, -0.02)), and extra-pyramidal side effects ( β = -0.34, 95% CI: (-0.59, -0.09)) were factors negatively associated with attitude towards antipsychotic medication treatment. Insight to illness ( β = 0.24, 95% CI: (0.20, 0.27) was a factor positively associated with attitude towards antipsychotic medications. Conclusion . The result suggests that the mean score of participants' attitude towards antipsychotic medications was good. Prevention of side effects particularly due to first generation antipsychotics is necessary.